O Programa Nacional de Apoio à Modernização da gestão e do planejamento dos estados e Distrito Federal (PNAGE) e seus resultados no Estado do Ceará - Costa Junior, Augusto César (2014)
Financed with funds from the Inter American Development Bank (IDB) and the participants' hand, the National Program to Support Modernization of Management and Planning of the states and the Federal District (PNAGE) aimed to improve the effectiveness and transparency of government institutions the states and the Federal District, in order to achieve greater efficiency of public spending. This paper assesses the PNAGE and their results for the State of Ceará, through the analysis of its financial performance and perception of the States Parties on the results measured through a questionnaire applied by the final evaluation of the National PNAGE. We conclude that despite their objectives were only partially achieved, the program provided the foundation techniques and materials to achieve a managerial public administration focused on effectiveness and transparency of public policies.